Effect of skin-to-skin contact on parents’ sleep quality, mood, parent-infant interaction and cortisol concentrations in neonatal care units: study protocol of a randomised controlled trial - Angelhoff, Charlotte (BMJ Open, 2018)
INTRODUCTION: Separation after preterm birth is a major stressor for infants and parents. Skin-to-skin contact (SSC) is a method of care suitable to use in the neonatal intensive care unit (NICU) to minimise separation between parents and infants. Less separation leads to increased possibilities for parent-infant interaction, provided that the parents’ sleep quality is satisfactory. We aimed to evaluate the effect of continuous SSC on sleep quality and mood in parents of preterm infants born <33 weeks of gestation as well as the quality of parent-infant interaction and salivary cortisol concentrations at the time of discharge. METHODS AND ANALYSIS: A randomised intervention study with two arms—intervention versus standard care. Data will be collected from 50 families. Eligible families will be randomly allocated to intervention or standard care when transferred from the intensive care room to the family-room in the NICU. The intervention consists of continuous SSC for four consecutive days and nights in the family-room. Data will be collected every day during the intervention and again at the time of discharge from the hospital. Outcome measures comprise activity tracker (Actigraph); validated self-rated questionnaires concerning sleep, mood and bonding; observed scorings of parental sensitivity and emotional availability and salivary cortisol. Data will be analysed with pairwise, repeated measures, Mann Whitney U-test will be used to compare groups and analysis of variance will be used to adjust for different hospitals and parents’ gender. ETHICS AND DISSEMINATION: The study is approved by the Regional Research Ethics Board at an appropriate university (2016/89–31). The results will be published in scientific journals. We will also use conferences and social media to disseminate our findings. TRIAL REGISTRATION NUMBER: NCT03004677.